PENGARUH SELF-SERVICE TECHNOLOGY QUALITY TERHADAP LOYALITAS DENGAN KEPUASAN SEBAGAI VARIABEL MEDIASI (STUDI PADA PELANGGAN MCDONALD'S DI SURABAYA) - Rosyidah, Nuraini; Andjarwati, Anik Lestari (Universitas Pendidikan Indonesia, 2021)
Recently, McDonald’s Indonesia have launched self-service technologhy by replacing manual cashier with self-ordering kiosk. To find out the impact of the self-service technologhy that have been adopted in McDonald’s Indonesia, this study proposed and tested the affect of self-service technologhy quality toward loyalty with satisfaction as mediating variable. The aim was based on the supposition that an overall quality of the self-service technologhy will influence satisfaction and loyalty toward McDonald’s that use the new technologhy. This research used 200 samples and used judgemental sampling method. Method of Data collection is done by distributing online questionnaires. The technique of data analysis used in this research is the path analysis technique. The results showed that self-service technologhy quality had a positive effect on loyalty and satisfaction proved to be a mediating variable. These results provide insights for the other enterprise to investment in the new technology in order to enhance the consumer experience, satisfaction, and loyalty.